Fundamentos bíblico-teológicos da capelania hospitalar : uma contribuição para o cuidado integral da pessoa - Hoepfner, Daniel (2008)
Pastoral care in the context of hospital visiting is entitled hospital chaplaincy. The initial three chapters of this paper analyze themes which are the biblical theological foundations of hospital chaplaincy. The first deals with the concept of taking care, the meaning of this action and its importance towards human life grounded on the theology of imago Dei, according to Genesis1.26-27. The second part of the paper presents the human being based on the biblical anthropology and the concepts of soul, heart, flesh and body. These anthropological notions present the human being solely in terms of existence and as a live unit animated by God. The third part describes the features of pastoral action related to the concept of pastoral care. The term refers to the metaphor of pastoralising the herd of God and is founded by the biblical image of God-shepherd and Christ as the good shepherd. Therefore, the chapter sheds light to conceptualizing, mainly from John 10, the pastoral ministry of Christ, as well as it introduces the pastoral care ministry as a means of expression of the Christian community along the history of the Church. The fourth chapter is briefly developed under a historical perspective of the hospital, it aims at grounding the hospital assistance as a human act from the theme of human dignity. Moreover, it leads to the necessity of integral care to the patient. The paper finishes by approaching the beginnings of Clinical Pastoral Training and its borders to psychology, it also ends by presenting the contents which were described in the previous chapters as biblical theological foundations of hospital chaplaincy: the human dignity, the biblical anthropology and the pastoral ministry of Christ.